Session Review: SAA General Session, Experimental Archaeology 2018 - Yvette A Marks (EXARC Journal)
The Society for American Archaeology is, perhaps with the exception of the World Archaeology Congress, the largest meeting of archaeologists in the world. The 2018 annual meeting was held in Washington DC and was attended by approximately 5000 archaeologists. Delegates were primarily from the States, but there was also a good international showing with attendees coming from around the world.